Maintain Of Environment From Affection Of CO2 ‐ A Review - Namdar, Abdoullah (University POLITEHNICA Timisoara, 2014)
Maintain environment is priority to any plan in human life. It is aimed to review of injection, storage and leakage monitoring of CO2 by using experimental, numerical and analytical data. The mineralogy, chemical composite, lithology, seismic wave propagation, small earthquake, accelerating natural earthquake, thermal stress‐strain modeling, ground movement level and risk assessment in this industry and fault activation have been discussed. It expects to better understand problems and research requirements related to this industry.